Mudanças nas concepções e ações docentes: processo de integração de computadores portáteis ao currículo - Gonçalves, Lina Maria (2015)
This work is linked to the Graduate Program in Education: Curriculum of Pontifical Catholic University of São Paulo (PUC-SP), and aims to understand possible changes in the concepts and practices of the participating teachers in the training Program One Computer per Student in the state of Tocantins (PROUCA TO) in curriculum, Digital Information and Communication Technologies (DICT) and DICT integration of the school curriculum in order to clarify the conceptual changes and / or attitudinal (especially those changes indicative of innovation evidence in the curriculum). The research was developed in two primary schools (EF), in the municipality of Gurupi / TO, using mainly methods and techniques of qualitative research, following the spiral of Elliott research-action. It used documental analysis (Proposal of the curriculum of the Municipality, Political-Pedagogical Projects - PPP and Thematic Projects of Schools, Projects and Teaching Plans); entry questionnaires and exit interviews with the four participating research teachers. Also, participant observation was performed in the moments dedicated to planning and development of these teachers classes and their actual classes, using laptops. A sample of lessons observed was videotaped and used in interviews of recollection stimulation in order to cause reflection on the teaching moments of action. Data were organized with the support of NVivo software and subjected to content analysis in the following categories: Conception of curriculum; Educational use of DICT; Curriculum integration of TDIC; and DICT changes or Innovation s Evidence. The latter was composed of four sub-categories adapted from Pacheco: Type of Decision, Educational Aspects, Sources of Information and Teacher Awareness, especially for the analysis focused on recollection stimulation interviews in order to understand the evolution of thought of teachers (initial behavior and reconsidered) in relation to the actions developed with the use of laptops. As main results, it is important to distinguish between two directions, in the observed changes (in the concepts and in the pedagogic actions). Changes were observed in dichotomous concept of the teachers between curricular and extracurricular activities to the prospect of integration between the two groups of activities. There have also been changes in the design of occasional use of laptops for integrated use in the school curriculum. Regarding the teachers' actions, the highlights were three levels changes in the use of laptops: from curriculum addendum to use as didactic and pedagogical resource; from use as reinforcing content to use as feature didactic and pedagogical; from didactic use and pedagogical resource to the integrated use in the school curriculum. The relevance of changes in teaching concepts is highlighted, as they subsidized their approach of integration of digital technologies in the school curriculum, creating conducive environment for the innovation in the curriculum